Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

sir/mam plzz solve this question i have attached here

sir/mam plzz solve this question i have attached here

Question Image
Grade:12th pass

1 Answers

Aditya Gupta
2080 Points
one year ago
dear student, this ques is based directly on DESCARTEs KISSING CIRCLES THEOREM.
(you can google it and look up the wikipedia article for more info and refer the SPECIAL CASES section).
also, lets call 1/r1, 1/r2, …..., 1/rn as p(1), p(2),......., p(n)
by the theorem, we have
p(k)= 1+p(k-1) ± 2sqrt(1.p(k-1))= (1 ± sqrtp(k-1))^2 (coz for unit circle p= 1/r= 1/1= 1)
so sqrtp(k)= 1 ± sqrtp(k-1) now since clearly rk is less than r(k-1), we get that p(k-1) is less than p(k). also, each pk is greater than 1. taking these facts into consideration, it is easy to see that – ve sign is rejected. 
hence, sqrtp(k)= 1 + sqrtp(k-1) 
or p(k)= (1 + sqrtp(k-1))^2.
now, how do we find p(1)?
clearly, it would be p(1)= (1 + sqrtp(0))^2
but we havent defined p(0) till now. but we know from the theorem that it would be 1/r0 where r0 is radius of circle used for tangency to C1 apart from S1. hence r0 is radius of S2= 1
so, p(0)= 1/1= 1
so, p(1)= 4
similarly p(2)= (1+2)^2= 9 etc. u clearly observe the pattern p(k)= (k+1)^2 (you can rigorously prove this using induction too)
hence, Lt (p1+p2+.....+pn)/n^3
= Lt (4+9+.....(n+1)^2)/n^3
= Lt (1+4+9+.....(n+1)^2)/n^3 – Lt 1/n^3
= Lt (n+1)(n+1+1)(2(n+1)+1)/6n^3 – 0
= Lt (1+1/n)(1+2/n)(2+3/n)/6
= 1*1*2/6
1/3 = p/q
Hence p+q= 1+3
4
KINDLY APPROVE :))

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free